2010
DOI: 10.1180/claymin.2010.045.4.489
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the organic groups of difunctional silanes on the preparation of coated clays for olefin polymer modification

Abstract: Sodium montmorillonite (MMT) was organically modified with hexadecyltrimethyl-ammonium ions and subsequently treated with dichlorosilanes and water, aimed at in situ silane condensation polymerization and modification of clay platelets by polysiloxane coatings. Dimethyldichlorosilane, methylphenyldichlorosilane, and diphenyldichlorosilane were used to produce three siloxane-modified organoclays. The structure and morphology of the clay materials were characterized by X-ray diffraction (XRD), Fourier transform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
3
5
0
Order By: Relevance
“…This can be the result of higher clay dispersion caused by the in situ generation of oligomers into the organophilic clay. These results are in agreement with previous scanning electron microscopy studies of these additives (Monasterio et al, 2010).…”
Section: Structural Characterization Via Temsupporting
confidence: 83%
See 2 more Smart Citations
“…This can be the result of higher clay dispersion caused by the in situ generation of oligomers into the organophilic clay. These results are in agreement with previous scanning electron microscopy studies of these additives (Monasterio et al, 2010).…”
Section: Structural Characterization Via Temsupporting
confidence: 83%
“…These results are in agreement with the GPC results (Monasterio et al, 2010 (Table 2) and they explain the above mentioned viscosity decrease ( Figure 5). Interestingly in group II, dimers were synthesized and the chemical nature of the interaction was similar.…”
Section: Structural Characterization Via Rheological Analysissupporting
confidence: 82%
See 1 more Smart Citation
“…When a solvent accessible Mg is substituted at the edge, the average number of H-bonds between the water and the bridging oxygen was inverted Si and non-octahedral Al structures were stabilized by water bridging H-bonds reported for the pyrophyllite edge surface [37,38]. Although experiments have not y direct evidence of an inverted Si in 2:1 dioctahedral phyllosilicates, the alternative EF st in principle, explain some inconsistencies in smectite reactivity [63][64][65]. A rec thermodynamics study based on DFT has suggested that these inverted Si at t pyrophyllite are possible defect structures at the AC edge of 2:1 phyllosilicates [61].…”
Section: Discussionmentioning
confidence: 99%
“…The size of large clay particles and the low affinity of natural clays to most organic polymers diminish their reinforcing ability in CPN (Bergaya et al, 2011). It is important to make the particles compatible via organophylization to facilitate their intercalation with the hydrophobic polymer macromolecules (He et al, 2005), in order to improve the clay dispersion in the matrix and enhance efficiency in modifying the final properties (Akelah and Moet, 1996;Zhu and Xanthos, 2004;Park et al, 2004;He et al, 2005;Joo et al, 2008;Qian et al, 2009;Daniel et al, 2008;Monasterio, 2010;Das et al, 2011;Bergaya et al, 2011). While both the basal spacing and the chemical affinity of silicate layers are important for their dispersion, two approaches are used for clay modification: interlayer ion exchange with surfactant, and treatment of functional groups on the clay surface and edges by organic compounds such as silane (Hussain et al, 2006;Shen et al, 2007;Joo et al, 2008;Daniel et al, 2008;Qian et al, 2009;Monasterio, 2010;Bergaya et al, 2011).…”
Section: Introductionmentioning
confidence: 99%